PERDAGANGAN DAN MISTISISME DALAM ISLAMISASI DI SUMATERA DAN JAWA - Masyhudi (Berkala Arkeologi, 2003)
The trade relations between Europeans and the Middle East, which have colored the trade map before the Islamic era, show that trade relations between Europe and Asia have been going on since before the times of Jesus Christ. Then after the collapse of the domination of India and China, due to the conquest of northern India which then spread to the South and the invasion of China by Islamic armies in the Middle East, it appeared that a wave of Arabs began to form colonies for traders. The trade and political relations between China and Persia, China with Srivijaya, India with Srivijaya and India with China were relations that had lasted for centuries. This kind of relationship cannot just be erased. Therefore, when the teachings of Muhammad (Islam) became established in the Middle East and came to power in northern India, the flow of international trade was intensified, as did the teachings of Islam itself.